Comparison of FSH and hMG on ovarian stimulation outcome with a GnRH antagonist protocol in younger and advanced reproductive age women. (11th July 2014) - Tabata, Chisa; Fujiwara, Toshihiro; Sugawa, Miki; Noma, Momo; Onoue, Hiroki; Kusumi, Maki; Watanabe, Noriko; Kurosawa, Takako; Tsutsumi, Osamu
Abstract: Purpose: To compare the embryo outcomes of in vitro fertilization/intra‐cytoplasmic sperm injection with a gonadotropin‐releasing hormone (GnRH) antagonist protocol with follicle stimulating hormone (FSH) and with human menopausal gonadotropin (hMG). Methods: We performed a retrospective cohort study in 465 patients. Stimulation was started by daily FSH injection, and either FSH was continued (FSH alone group) or hMG was administrated (FSH‐hMG group) after administration of a GnRH antagonist. Primary outcomes were the embryo profile (number of retrieved, mature, and fertilized eggs, and morphologically good embryos on day 3) and endocrine profile. Secondary outcomes were the doses and durations of gonadotropin. Data were stratified by the patients' age into two groups: <35 years and ≥35 years. Results: In patients aged <35 years, the number of retrieved oocytes in the FSH alone group was significantly increased than that in the FSH‐hMG group (13.7 vs 9.2, P = 0.04), while there was no difference at other age groups. The FSH‐hMG group required a significantly greater amount of gonadotropins at any age (all ages, P < 0.001; <35 years, P = 0.013; ≥35 years, P < 0.001). Conclusions: Exogenous FSH alone is probably sufficient for follicular development and hMG may not improve the embryo profile in a GnRH antagonist protocol across all age.